Practical English 3 - Harris, Tim (Harcourt Brace Jovanovich, 1988)
This enjoyable three-level series provides a solid grounding in the structures and communicative functions of English, as well as extensive practice in speaking, listening, reading, and writing
Keywords: English language / Grammar / Problems, exercises, etc; English language / Textbooks for foreign speakers; Anglais (Langue) / Manuels pour allophones; English language; English language / Grammar; Problems and exercises; Textbooks / for foreign speakers